Dating archaeological copper using electrochemical impedance spectroscopy. Comparison with voltammetry of microparticles dating. Issue 2 (7th April 2015) - Doménech‐Carbó, A.; Capelo, S.; Piquero, J.; Doménech‐Carbó, M. T.; Barrio, J.; Fuentes, A.; Al Sekhaneh, W.
Abstract : A methodology for dating copper/bronze archaeological objects aged under atmospheric environments using electrochemical impedance spectroscopy (EIS) is described. The method is based on the measurement of resistance associated to the growth of corrosion layers in EIS recorded upon immersion of the pieces in mineral water and applying a bias potential for the reduction of dissolved oxygen. Theoretical expressions for the time variation of such resistance following a potential rate law are presented. Equivalent expressions are derived and applied for estimating the variation of the tenorite/cuprite ratio from their specific voltammetric signals using voltammetry of microparticles data. Calibration curves were constructed from a set of well‐documented coins.